2003
DOI: 10.1074/jbc.m302162200
|View full text |Cite
|
Sign up to set email alerts
|

Expression Level of the Canonical Transient Receptor Potential 3 (TRPC3) Channel Determines Its Mechanism of Activation

Abstract: Studies on the mechanism of activation of canonical transient receptor potential (TRPC) channels have often yielded conflicting results. In the current study, we have investigated the influence of expression level on the mode of regulation of TRPC3 channels. At relatively low levels of expression in DT40 chicken B-lymphocytes, TRPC3 was activated by the depletion of Ca 2؉ stores. Expression was increased by either transfecting with a 10-fold greater concentration of plasmid or transfecting with TRPC3 under con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
122
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 35 publications
8
122
1
Order By: Relevance
“…While the lack of a correlation between the Li-induced decrements in the latter functional measure and TRPC3 immunolabeling relative to vehicle-treatment seems to conflict with this conclusion, it is not clear yet whether global TG-induced Ca 2 þ mobilization changes in direct proportion to the levels of TRPC3. The functional effects of TRPC3 in modulating SOCE have been shown to vary in relation to its expression levels: 23 at low levels TRPC3 operates as an SOCC, whereas at high expression levels it shows G protein receptor-coupled phospholipase C-operated characteristics. 21 The notion that pathophysiologically and diagnostically distinctive Ca 2 þ homeostasis abnormalities occur in BD-I disorder has grown out of series of observations of differential changes in indices of Ca 2 þ dynamics measured in surrogate peripheral blood cell and BLCLs models from BD, comparison mood and nonmood disorder patients, and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the lack of a correlation between the Li-induced decrements in the latter functional measure and TRPC3 immunolabeling relative to vehicle-treatment seems to conflict with this conclusion, it is not clear yet whether global TG-induced Ca 2 þ mobilization changes in direct proportion to the levels of TRPC3. The functional effects of TRPC3 in modulating SOCE have been shown to vary in relation to its expression levels: 23 at low levels TRPC3 operates as an SOCC, whereas at high expression levels it shows G protein receptor-coupled phospholipase C-operated characteristics. 21 The notion that pathophysiologically and diagnostically distinctive Ca 2 þ homeostasis abnormalities occur in BD-I disorder has grown out of series of observations of differential changes in indices of Ca 2 þ dynamics measured in surrogate peripheral blood cell and BLCLs models from BD, comparison mood and nonmood disorder patients, and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent research directed at elaborating the molecular components and/or mechanisms mediating SOCE and ROCE highlights the key role of several members of the TRP family of cation permeable channels in these processes in nonexcitable cells, such as lymphocytes and platelets. [21][22][23] This superfamily of proteins is comprised of three branches distinguished by sequence homology and functional similarities: TRPC (canonical), TRPV (vanilloid) and TRPM (melastatin). 24 Two subgroups within the canonical branch, (TRPC1,4&5 and TRPC3,6&7, respectively) have been implicated in SOCE and ROCE, 24,25 raising the prospect of the involvement of one or more of these TRPC members in the Ca 2 þ abnormalities that have been reported in BD and the in actions of Li in BLCLs highlighted above.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies also demonstrated that TRPC channels did not operate as SOCE channels, but rather are gated by second messengers like Ca 2+ or diacylglycerol (DAG; [15][16][17]). Hence, the involvement of TRPC channels in the SOCE mechanism is a controversial issue, and appears to dependent on the cell types investigated, and importantly on the expression level of the TRPC [14,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the last case, store-operated Ca 2ϩ entry (SOCE) is triggered by depletion of SR Ca 2ϩ stores (6,41,42,49,55,56). We and others have shown that different transient receptor potential channel (TRPC) isoforms are expressed in ASM (6,58).…”
mentioning
confidence: 99%